2016
DOI: 10.1021/acs.iecr.6b00978
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Wastes from the Production of Alumina-Based Catalyst Carriers

Abstract: Preparation of microspherical chromia−alumina KDM-type catalysts for alkane dehydrogenation is based on utilization of an amorphous nanostructured hydroxide−oxide Al 2 O 3 −x(OH) 2 •nH 2 O (where x = 0−0.28, n = 0.03−1.8) prepared via the centrifugal thermal activation (CTA) of gibbsite. The fine fraction of this carrier is considered as industrial waste, requiring efficient recycling options, which are explored in this work. A range of physicochemical methods was applied to analyze the main properties (phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In addition, a sharp drop of the baseline after 40°2θ indicated the presence of a certain amorphous phase. 35 Figure 3 depicts the diffractograms of the CTA samples after heat-treatment at 650, 750, and 850 °C. According to the phase analysis, a metastable form of crystalline alumina with the cubic structure known as γ-phase prevailed in the CTA-product treated at 650 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a sharp drop of the baseline after 40°2θ indicated the presence of a certain amorphous phase. 35 Figure 3 depicts the diffractograms of the CTA samples after heat-treatment at 650, 750, and 850 °C. According to the phase analysis, a metastable form of crystalline alumina with the cubic structure known as γ-phase prevailed in the CTA-product treated at 650 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The broad diffraction peak at 67.1° 2θ suggested that the sample contained also a well-dispersed phase of Al 2 O 3 . In addition, a sharp drop of the baseline after 40° 2θ indicated the presence of a certain amorphous phase …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sodium aluminate solution is mainly derived from the Bayer process or the alkaline process of smelting bauxite. Additionally, with the increasing demands for environmental protection and the development of resource recycling, businesses not only smelt bauxite but also are now utilizing aluminum-rich fly ash, , coal gangue, red mud, , waste alumina, ,, and nuclear-contaminated sludge ,, to extract aluminum to produce sodium aluminate solution. Due to variations in raw materials and processing techniques, the concentration and component ratios of sodium aluminate solution differ, thereby influencing the process and reaction conditions of carbonate reaction to produce pseudoboehmite, consequently affecting process control and the properties of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Another feature of this study is that the catalyst support is produced using a waste-free and reagentless technology by thermal activation of gibbsite. 15 This technology results in the particle size of alumina in the range of 40-100 μm allowing thus the dehydrogenation to be carried out using a fluidized-bed reactor. The thermal activation method is based on the transformation of nonporous crystalline gibbsite (Al(OH) 3 ) into an amorphous product via pulsed heating of gibbsite on a metallic preheated surface (or in a gas flow) to the temperature of dehydration, which is followed by a rapid cooling step.…”
mentioning
confidence: 99%